Assessment of health-related quality of life in children with functional defecation disorders - Faleiros, Francisca Teresa Veneziano [UNESP] (2006)
Objective: To evaluate the health-related quality of life in children with functional defecation disorders. Methods: One hundred children seen consecutively were enrolled and subdivided into three subsets according to the Roma II classification criteria: functional constipation (n = 57), functional fecal retention (n = 29) and nonretentive functional soiling (n = 14). The generic instrument Child Health Questionnaire - Parent Form 50 (CHQ-PF50®), was used to measure quality of life and to assess the impact of these disorders from the point of view of parents. The instrument measures physical and psychosocial wellbeing in 15 health domains, each of which is graded on a scale from 0 to 100, with higher values indicating better health and greater wellbeing. Ten of these are then used to obtain two aggregated and summary scores: the physical and psychosocial scores. Results: No statistically significant differences were detected between subsets in terms of demographic or anthropometric characteristics. In 14 domains, children with defecation disorders scored lower than healthy children. When subsets were compared, statistically significant differences were detected between children with nonretentive functional soiling (lower scores) and those with functional constipation. Physical and psychosocial scores for the entire sample were lower than those for the group of healthy children used as controls. Conclusions: The CHQ-PF50® was considered adequate for demonstrating compromised quality of life in children with functional defecation disorders, as has been reported for other diseases, being a useful tool for making treatment decisions and for patient follow-up. Copyright © 2006 by Sociedade Brasileira de Pediatria.